Customer Behavior Analysis in the Adoption of Islamic Banking Products: An Empirical Study on Trust, Religiosity, and Service Quality - Sadly, Effendi; Agustami, Eli; Effendi, Syamsul (International Journal of Economics (IJEC), 2025)
This study explores customer behavior regarding the adoption of Islamic banking products, emphasizing the roles of trust, religiosity, and service quality. Utilizing a quantitative research approach, data were collected from a diverse sample of Islamic banking customers through structured questionnaires. The findings reveal that trust significantly influences customer decisions to adopt Islamic banking products, while religiosity enhances this relationship by fostering a deeper commitment to Islamic financial principles. Additionally, service quality emerged as a critical factor, shaping customer satisfaction and loyalty. This empirical study contributes to the understanding of consumer behavior in Islamic finance and offers insights for banking institutions to enhance their strategies in attracting and retaining customers. The implications of these findings highlight the necessity for Islamic banks to cultivate trust, address the spiritual needs of customers, and prioritize high service quality to succeed in a competitive market.